THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEM APPLICATION ON REGIONAL TAX INCOME ACCOUNTABILITY IN REGIONAL REVENUE OFFICE CIMAHI - Hasna Safira; Purwanto (LPPM POLITEKNIK LP3I BANDUNG, 2018)
This research was conducted in Regional Revenue Office Cimahi, one of government agencies engaged in regional revenue area. The phenomenon that occurs was that the accountability in Cimahi Government had not been optimal yet. The purpose of this research was to determine the influence of Accounting Information System application on regional tax income accountability in Regional Revenue Office Cimahi. Descriptive and verification methods were used in this research. The statistical test used were Pearson correlation, regression analysis, determination coefficient, hypothesis test, validity test, reliability test, and SPSS as software tool. Results showed that Accounting Information System application on regional tax income accountability in Regional Revenue Office Cimahi is categorized as “enough” and there was a close and one way relationship between Accounting Information System with regional tax income accountability, by showing that H0 was rejected and Ha was accepted, which means, Accounting Information System application influenced regional tax income accountability in Regional Revenue Office Cimahi